Climate change impacts on hydrology, upstream water dependencies and crop production in the Asian Mega-Deltas - Biemans, Hester; de Miguel Garcia, Angel; Gülpen, Marijn; Islam, Feroz; van Scheltinga, Catharien Terwisscha; Nelson, Katherine; Mondal, Manoranjan; Urfels, Anton (International Rice Research Institute, 2024)
This research brief explores the interplay between water and food systems in the Ganges-Brahmaputra-Meghna and Mekong River basins, highlighting regional dynamics and climate change impacts. To do so, a hydrology-vegetation model is used. Based on the climate change scenarios chosen in this study, in the Ganges-Brahmaputra- Meghna basin, future water inflows are projected to rise, while in the Mekong, large dam expansions are expected to decrease wet-season flooding and increase dry-season flows. Both basins have sufficient water availability to meet full irrigation demands, excluding other sectoral and ecological needs now and in the future. However, during the dry season, the simulated agricultural water withdrawal in the deltas suppose an important part of the water inflows, making clear that deltas’ inflows during the dry season in both basins are highly sensitive to upstream irrigation abstractions, which are already substantial and projected to remain so by 2050. Upstream irrigation intensification puts at the risk the downstream deltas by increasing water scarcity and complicating water allocation for other sectors, including ecosystems. Climate change impacts on food production varies significantly accordingly to the model set-up: in the Ganges-Brahmaputra-Meghna, where land use change is considered but with no variation of CO2 concentration, yields are expected to decline due to heat stress on non-rice cereals; whereas in the Mekong, where land use change is considered constant but with variation of CO2 concentration, the effect of CO₂ fertilization limited heat stress for rice, enhancing productivity. Key adaptation challenges include improving groundwater management and promoting sustainable upstream cropping intensification in the Ganges-Brahmaputra- Meghna without deteriorating downstream water stress. In the Mekong, adaptations must address altered flooding patterns, including reduced riverine flooding and increased erratic flash floods, which could impact the Cambodian floodplains and Tonle Sap. Equitably distributing increased streamflow, to mitigate salinity intrusion in the delta while supporting upstream agricultural intensification, is also critical. This study underscores the need for integrated basin-scale water management to navigate these challenges sustainably.